(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The article discusses the effectiveness of the impulse method of timber impregnation to improve its operational properties when used in building structures. A detailed analysis of modern timber impregnation methods is presented, in particular, the traditional static and the proposed impulse methods. The main advantages of impulse impregnation technology are defined, such as increasing the durability and fire resistance of wood, as well as improving its physical and mechanical properties, depending on the type of impregnation composition used. In the course of the study, an experimental comparison of both methods was carried out, the results of which confirm the high efficiency of the pulsed infiltration method. The materials and methods used for the experiments are described, including wood characterization and the pulsed impregnation process. A detailed description of the proposed technology of impulse impregnation of wood is given. The results of the research can be used to improve wood processing methods and increase its operational properties in building structures, which contributes to more efficient and widespread use of timber as a building material. The purpose of this study is to develop and optimize the method of impulse impregnation of wood to improve its properties when used in building structures. The research is aimed at identifying the effectiveness of the impulse method in comparison with the static method of timber impregnation. In the conducted research, a detailed description of an effective method of wood modification for building structures, which is implemented using the technology of impulse impregnation of wood with technological compositions, was proposed and performed. This technology allows you to intensify the wood processing process, increase the penetration depth of the impregnating liquid into the pores of the wood and ensure a more even distribution of the liquid in the wood structure. This is important for increasing the durability and operational properties of wooden structures depending on the type of impregnation composition (for example, fire resistance, biological resistance, strength, hydrophobicity). The obtained experimental data prove the positive effect of the impulse component of pressure on increasing the depth and achieving homogeneity of penetration of the impregnating liquid into the capillary-porous structure of wood. Keywords: wooden structures; building materials; fire protection; biological protection; impregnation; saturation; capillary-porous body.